Analisis Pengaruh Sektor Pariwisata dan Kontribusinya Terhadap Pendapatan Asli Daerah (PAD) Kabupaten Bangkalan - Imron; Ririt Iriani Sri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study analyzes the influence of the tourism sector and its contribution to the PAD of Bangkalan Regency. BPS reports in figures and Bangkalan Regency budget realization reports are the secondary data sources used in this quantitative research. The analysis in this study was conducted using multiple linear regression analysis methods. This analysis was carried out using the SPSS program. The results showed that the number of tourist visits had a significant effect on Regional Original Revenue (PAD), while the number of tourist attractions and hotel occupancy had no significant effect on Bangkalan Regency PAD.